Characterizing bacterial communities in Phragmites australis rhizosphere and non-rhizosphere sediments under pressure of antibiotics in a shallow lake - Zhang, Ling; Bai, Junhong; Zhang, Kegang; Wei, Zhuoqun; Wang, Yaqi; Liu, Haizhu; Xiao, Rong; Jorquera, Milko A. (Frontiers in Microbiology, 2022)
Antibiotics are ubiquitous pollutants and widely found in aquatic ecosystems, which of rhizosphere sediment and rhizosphere bacterial communities had certain correlation. However, the response of bacterial communities in P. australis rhizosphere and non-rhizosphere sediments to antibiotics stress is still poorly understood. To address this knowledge gap, the samples of rhizosphere (R) and nonrhizosphere (NR) sediments of P. australis were collected to investigate the differences of bacterial communities under the influence of antibiotics and key bacterial species and dominate environmental factors in Baiyangdian (BYD) Lake. The results showed that the contents of norfloxacin (NOR), ciprofloxacin (CIP) and total antibiotics in rhizosphere sediments were significantly higher than that in nonrhizosphere sediments, meanwhile, bacterial communities in nonrhizosphere sediments had significantly higher diversity (Sobs, Shannon, Simpsoneven and PD) than those in rhizosphere sediments. Furthermore, total antibiotics and CIP were found to be the most important factors in bacterial diversity. The majority of the phyla in rhizosphere sediments were Firmicutes, Proteobacteria and Campilobacterota, while Proteobacteria, Chloroflexi was the most abundant phyla followed by Bacteroidota, Actinobacteriota in nonrhizosphere sediments. The dominate factors of shaping the bacterial communities in rhizosphere were total antibiotics, pH, sediment organic matter (SOM), and NH4-N, while dissolved organic carbon (DOC), NO3-N, pH, and water contents (WC) in nonrhizosphere sediments. It is suggested that antibiotics may have a substantial effect on bacterial communities in P. australis rhizosphere sediment, which showed potential risk for ARGs selection pressure and dissemination in shallow lake ecosystems.